Public pensions and capital accumulation : the case of Brazil - Gerhard Glomm; Jürgen Jung; Changmin Lee; Chung Tran (Center for Economic Studies and ifo Institute (CESifo), 2005)
We use an OLG model to study the effects of the generous public sector pension system in Brazil. In our model there are two types of workers, one working in the private sector, the other working in the public sector. Public workers produce infrastructure or education services. We find that reducing generosity of the public sector pensions has large effects on capital accumulation and steady state income.
Keywords: H55; H41; E62; 330; pension reform; capital accumulation; Ruhegehalt; Rentenreform; Wirtschaftspolitische Wirkungsanalyse; Investition; Brasilien